PENGARUH FREKUENSI INTERAKSI DAN VOLUME INTERAKSI ANTAR INFLUENCER TERHADAP VISIBILITAS KONTEN PADA MEDIA TIKTOK - Nabil Amarullah; Nazwa Difa Naila; Nazwa Salsabila; Zahra Agniasari; Syiti Sarah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Interactions between influencers on TikTok play an important role in increasing content visibility.This study analyzes the correlation between the frequency and volume of interactions between influencers and the level of content visibility using secondary data obtained through content analysis on TikTok.Data was collected from various influencer accounts by observing interaction metrics such as views, comments, likes, and shares. Correlational analysis was conducted to identify the relationship between interaction intensity and content distribution on the platform.The results showed a significant positive correlation between interaction levels and increased content reach, where more frequent interactions tend to increase algorithmic exposure. This study provides insights for influencers and digital marketers in optimizing interaction strategies to increase audience engagement and content reach on TikTok.